Growth and Switching of Ferroelectric Nanocrystals from Ultrathin Film of Copolymer of Vinylidene Fluoride and Trifluoroethylene - R. Gaynutdinov; V. Fridkin; H. Kliem (Journal of Nanotechnology)
The ferroelectric nanocrystals of the copolymer of vinylidene fluoride and trifluoroethylene P(VDF-TrFE) were grown from ultrathin Langmuir-Blodgett (LB) films on Si substrate. The annealing of ultrathin LB films with thickness of 3 monolayers (5 nm) in air in paraelectric phase at temperature 125∘C was performed. The self-assembly leads to the growth of nanocrystals of ferroelectric copolymer 15–25 nm thick and 100–200 nm in diameter. The nanocrystals presumably belong to orthorhombic space group, where axis 2 is the direction of spontaneous polarization (and normal to substrate). By means of atomic force microscopy (AFM), the kinetics of ferroelectric nanocrystals growth and their switching were investigated. The obtained results confirm the conclusions that copolymer nanocrystals are candidates for high-density nonvolatile storage media devices.